2005
DOI: 10.1037/h0100308
|View full text |Cite
|
Sign up to set email alerts
|

Three-tier models of reading and behavior.

Abstract: This paper provides a description of three-tier intervention models for reading and behavior. Although there is scientific evidence that the implementation of interventions at one or more levels of these models leads to improved reading or behavior performance, there is a paucity of research detailing the integration of three-tiered reading and behavior models. A future direction in the area of reading and behavior intervention models should be the integration of these models. This future direction is briefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Research suggests that high-quality intervention grounded in EBPs is likely to result in positive outcomes for young children with ASD (e.g., Wong et al, 2014). Nonetheless, many EBPs have failed to change the behavior of one or more participants in research studies (e.g., Stewart, Benner, Martella, & Marchand-Martella, 2007). Practitioners may need more information about which EBPs are likely to be effective for changing a specific target behavior, given the heterogeneity of the population and variation in intervention contexts.…”
mentioning
confidence: 99%
“…Research suggests that high-quality intervention grounded in EBPs is likely to result in positive outcomes for young children with ASD (e.g., Wong et al, 2014). Nonetheless, many EBPs have failed to change the behavior of one or more participants in research studies (e.g., Stewart, Benner, Martella, & Marchand-Martella, 2007). Practitioners may need more information about which EBPs are likely to be effective for changing a specific target behavior, given the heterogeneity of the population and variation in intervention contexts.…”
mentioning
confidence: 99%
“…While the primary features of PBIS implementation are the same regardless of instructional level and setting, implementation in high schools is complicated by contextual factors such as the focus on graduation requirements, supporting the transition from high school to post-school education and employment, and the unique social and emotional needs of PBIS IN HIGH SCHOOLS adolescents (Flannery, Frank, Kato, Doren, & Fenning, 2013). Further, few studies have focused on the effects of PBIS implementation at all 3 tiers in schools at any instructional level (Stewart, Benner, Martella, & Marchand-Martella, 2007). Understanding that the primary student variables that are associated with high school completion include attendance, behavior, and academic performance (Balfanz, Herzog, & Mac Iver, 2007;Hammond, Linton, Smink, & Drew, 2007), there is a need for in-depth research about how PBIS implementation and evidence-based social/emotional skills development can be implemented in high schools and improve student outcomes as they move into adulthood.…”
Section: Outcome Research Of Pbis Implementationmentioning
confidence: 99%
“…Tiered evidence-based strategies should be employed to improve the school system's capacity to support these students in mainstreamed placements using more intensive behavioral supports, rather than punitive or exclusionary management strategies (Evans, Harden, & Thomas, 2004;Farmer et al, 2007). A recent review identified 12 three-tiered behavioral intervention models with research support, suggesting that there are a number of evidence-based options for schools to choose from, including the widely diffused School-wide Positive Behavioral Support model (Stewart, Benner, Martella, & Marchand-Martella, 2007). Second, efforts should be made to support the implementation of evidence-based practices shown to improve the outcomes of children placed in REPs, as well as to avoid practices that are known to be ineffective (Simpson, Peterson, & Smith, 2011;Sutherland et al, 2008).…”
Section: Implications For Policy and Practicementioning
confidence: 99%